History Aware Anomaly Based IDS for Cloud IaaS - Gupta, Punit; Kaliyar, Pallavi (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Cloud Computing provides different types of services such as SaaS, PaaS, IaaS. Each of them have their own security challenges, but IaaS undertakes all types of challenges viz., network attack ,behaviour based attack, request based attacks i.e handling the requests from untrusted users, XSS (cross site scripting attack), DDOS and many more. These attacks are independent of each other and consequently the QoS provided by cloud is compromised. This paper proposes a History aware Behaviour based IDS (Intrusion Detection System) BIDS. BIDS provides detection of untrusted users, false requests that may lead to spoofing, XSS or DOS attack and many more such attacks. In addition, certain cases where user login or password is compromised. History aware BIDs can be helpful in detecting such attacks and maintaining the QoS provided to the user in cloud IaaS ( Infrastructure as a service).